Analisis Strukturalisme pada Cerita Legenda Keong Mas - Martha Amanda Sari; Aini Fitri Rohmatul Ilmi; Wawan Hermawan (Pragmatik : Jurnal Rumpun Ilmu Bahasa dan Pendidikan, 2026)
Oral literature is a form of storytelling from one individual to another in a concise manner as a representation of a society's culture. One type that is interesting to study in this field is legends. This study examines the Keong Mas legend using Burhan Nurgiyantoro's structuralism approach theory, which focuses on analyzing the relationship between intrinsic and extrinsic elements in literary works. This study uses a qualitative descriptive method that aims to reveal the narrative structure and social and cultural meanings contained in the legend as a reflection of the moral values and local wisdom of the people of East Java. The information collection method used observation and note-taking. The results of the analysis show that the Keong Mas legend has a cohesive story structure, including theme, characters, plot, setting, and point of view, which simultaneously reflect the values of loyalty, justice, and family conflict in a socio-cultural context. These findings confirm the relevance of oral literature as a medium for the inheritance of living and evolving cultural values, and contribute to the understanding of cultural identity and literary aesthetics in Indonesia, especially in the East Java region.